Influencing investment disputes from the outside - Joseph (Yusuf) Saei (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2017)
Non-disputing third party briefs have garnered much commentary in the investment arbitration literature. However, third parties, beyond knowing the doctrinal requirements and rules of brief submission, must be aware of the forms of activism often connected to brief submission, and should know how past third parties have funded their efforts.
Keywords: 330